Effectiveness of NTGD-Based E-Books on Students’ Analytical Thinking in Algebraic Derivatives Learning - Khusnul Khotimah; Ino Angga Putra (SCHOOLAR: Social and Literature Study in Education, 2026)
This study aims to analyze the effectiveness of an e-book based on the Numbered Team in Guided Discovery (NTGD) model in improving students’ analytical thinking skills on the topic of derivatives of algebraic functions. The research employed a quantitative approach using a pre-experimental one-group pretest–posttest design involving a single class of 25 students selected through purposive sampling. The research instrument consisted of an essay-type analytical thinking skills test measuring three indicators: the ability to identify problems, analyze relationships among concepts, and draw logical conclusions. Data were analyzed using the Shapiro–Wilk normality test and a paired-samples t-test at a significance level of 0.05. The results indicated that both pretest and posttest data were normally distributed and that there was a statistically significant difference between pretest and posttest scores, with a t-value of –13.171 and a Sig. (2-tailed) value of 0.000 < 0.05. These findings indicate that the use of the NTGD-based e-book had a significant effect on improving students’ analytical thinking skills on the topic of derivatives of algebraic functions. Therefore, the NTGD-based e-book is worthy of consideration as an alternative learning medium for developing higher-order thinking skills in mathematics learning.